2016
DOI: 10.3892/ol.2016.4093
|View full text |Cite
|
Sign up to set email alerts
|

Rare occurrence of cavitation of lung metastases following effective targeted therapy: A case report

Abstract: Abstract. The metastasis of malignant tumors to the lung is relatively common; however, cavitation of metastases is extremely rare in clinical cases, and the various mechanisms are controversial. The majority of irregular metastatic cavities form naturally and are detected incidentally when patients are examined prior to any therapeutic measures. The current study presents the case of a lung adenocarcinoma patient with total cavitation of intrapulmonary metastases following effective targeted therapy at the Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…If diffuse cystic lesions in a lung cancer patient are found after a relatively short period of time, the common radiological differential diagnoses include desquamative interstitial pneumonia, usual interstitial pneumonia, lymphocytic interstitial pneumonia, pneumocystis pneumonia, and pulmonary cystic metastasis [1]. A few reports have mentioned that metastatic lung adenocarcinoma presented as multiple thin-walled cavities [3-5]. Song et al [3] reported the occurrence of cavitation of lung metastases following EGFR-tyrosine kinase inhibitor therapy.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…If diffuse cystic lesions in a lung cancer patient are found after a relatively short period of time, the common radiological differential diagnoses include desquamative interstitial pneumonia, usual interstitial pneumonia, lymphocytic interstitial pneumonia, pneumocystis pneumonia, and pulmonary cystic metastasis [1]. A few reports have mentioned that metastatic lung adenocarcinoma presented as multiple thin-walled cavities [3-5]. Song et al [3] reported the occurrence of cavitation of lung metastases following EGFR-tyrosine kinase inhibitor therapy.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…A few reports have mentioned that metastatic lung adenocarcinoma presented as multiple thin-walled cavities [3-5]. Song et al [3] reported the occurrence of cavitation of lung metastases following EGFR-tyrosine kinase inhibitor therapy. They noted that these diffuse cystic changes on imaging can occur following effective targeted therapy.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Primary or metastatic solid lung tumours may develop cavities after chemotherapy. 18 19 Central necrosis and tumour cavitation following treatment with chemotherapeutic agents such as vascular endothelial growth factor inhibitors, which act by inhibition of angiogenesis, is indicative of good therapeutic response (figure 4). On the other hand, filling in of a cavity by regrowth of solid tumour may indicate tumour progression.…”
Section: Aetiologymentioning
confidence: 99%
“…Renal, bladder, and synovial sarcomas are far rarer causes for cavitation of metastasis to the lung. 3 We present a patient with an unusual presentation of hemoptysis with cavitary pulmonary lesions secondary to renal cell carcinoma metastasis.…”
Section: Introductionmentioning
confidence: 99%